2015
DOI: 10.2214/ajr.14.13148
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Secondary to Anterior Cervical Fusion: Radiologic Evaluation and Findings in 74 Patients

Abstract: Dysphagia is an underrecognized but significant complication of ACF. After ACF, 4.1% of patients presented for radiologic evaluation of dysphagia. Although ACF procedures are most frequently performed in the lower cervical spine, dysphagia is a more common clinical problem after ACF in the mid cervical spine. Radiologic examinations should be specifically tailored to evaluate ACF patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…The incidence of dysphagia within 1 week after anterior cervical spine surgery varies from 1% to 79%. [ 9 13 14 15 16 17 ] This wide variation may be attributed to differences in patient age and sex, surgical technique, extent of surgery, spine level, operative time, or use of spinal instrumentation. Bazaz et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of dysphagia within 1 week after anterior cervical spine surgery varies from 1% to 79%. [ 9 13 14 15 16 17 ] This wide variation may be attributed to differences in patient age and sex, surgical technique, extent of surgery, spine level, operative time, or use of spinal instrumentation. Bazaz et al .…”
Section: Discussionmentioning
confidence: 99%
“…analyzed a radiologic evaluation of modified barium swallow studies and esophagrams in 74 patients who demonstrated dysphagia secondary to ACF. [ 17 ] Serious complications of ACF that resulted in dysphagia included surgical hardware displacement or bone graft displacement, esophageal perforation, and retropharyngeal abscess. Pharyngeal functional abnormalities were detected in 50 patients (67.6%), with penetration, aspiration, or both, seen in 32 patients (43.2%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact cause of dysphagia in the traumatic spinal injury is still unknown as it is often multifactorial. This can include, but is not limited to, soft-tissue swelling, displacement of the esophagus and/or pharynx, damage to critical nerves from retraction and dissection, and hematoma [16, 17]. Sensory deficits as a result of damage to the pharyngeal branch of the vagus nerve or glossopharyngeal nerve may also be implicated due to the observation of silent aspiration and impaired cough reflex within this population [18].…”
Section: Discussionmentioning
confidence: 99%
“…Contrast oesophagography is the standard diagnostic tool for oesophageal perforation 16 and barium contrast oesophagography should be used if no perforation is detected. 17 , 18 This technique cannot be easily used in patients with cervical spine injury, however. Flexible oesophagoscopy has a sensitivity of 95.8–100% and a specificity of 92.4–100% in the evaluation of penetrating oesophageal injury and can provide a direct visualization of the perforation; it is thought to be a useful diagnostic tool with a good safety profile in the early evaluation of penetrating injuries.…”
Section: Discussionmentioning
confidence: 99%